Punicalagin Suppresses LPS-induced Inflammatory Responses in Murine Macrophages via JAK/STAT Signaling Pathway and Zymosan-induced Mice Paw Edema - Yan, Huan; Gulimire, Abilaiti; Zhu, Junyu; Liang, Huaping; Gu, Zhengyi (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: To investigate the anti-inflammatory activity of punicalagin (PUN) on mouse macrophages and the underlying mechanisms. Materials and Methods: Mouse primary peritoneal macrophages (PMs) were treated with lipopolysaccharide (LPS; 10μg/ml) and/ or PUN (50μM) for 4, 8 and 12 hr. The expression levels of inducible nitric oxide synthase (iNOS), interleukin (IL)-1β, IL-6, IL-12P40 and CCL-2 mRNAs were analyzed by qRT-PCR. Total iNOS, MAPK and JAK/STAT protein levels were measured by Western blotting and the secreted levels of IL-1β, IL-6, IL-12P40 and IL-1270 by ELISA. Acute paw edema was induced in mice with zymosan and the animals were treated with high (50 mg/kg), medium (25 mg/kg) and low (12.5 mg/kg) doses of PUN. The levels of IL-1β, IL-6, CCL-2 and other related inflammatory factors and chemokines in the mouse paw tissue homogenates were detected by ELISA. Results: Compared to the LPS-treated cells, PUN significantly decreased the levels of inflammatory cytokines and other factors (P<0.05). In addition, high dose of PUN down regulated p-ERK, p-JAK1, p-STAT1 and p-STAT3, without significantly affecting p-p38 and p-JNK. Finally, acute paw edema in the mouse model was alleviated within 12h of high-dose PUN administration, which also inhibited inflammatory cytokines and chemokines. Conclusion: PUN inhibits macrophage-mediated inflammation and the secretion of inflammatory cytokines/chemokines by targeting the ERK/MAPK and JAK/STAT signaling pathways.
Keywords: Punicalagin; LPS-induced Inflammatory Responses; Macrophages; JAK/STAT; Paw edema